åˆ©ç”¨å›¾ç‰‡æ•™å¦æé«˜å¦ç”Ÿæ±‰è¯åè¯å¦ä¹ çš„èƒ½åŠ› - Nirmala, Ayu; ., Ina; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
??????????????????????????????????????????????St. Fransiskus Asisi????????????39???????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????89.75%? ?????? ?? ??? Abstrak : The purpose of this research is to know the effect of teaching method with media images to the students and to understand the reaction of students about it. This object of this research is Senior High School St. Fransiskus Asisi students, with total students were 39 students. The research method are practice and test. Based on comparing the pre-test and post-test result images method can increase students??images??students ability get increase 89.75%. Keyword : Nouns, Images, Learning Method